Coconut varieties for more return - Niral, V; Jerard, B Augustine; Chowdappa, P (Indian Horticulture, 2018)
The research efforts have recorded impressive achievements in terms of developing new cultivars and production technologies, which when demonstrated in the field resulted in two-three fold increase in yield. On a national level, research efforts under the aegis of the ICAR, CPCRI, AICRP and SAUs have resulted in the development of 49 improved varieties, including 20 hybrid varieties, capable of producing 2.79-6.28 tonnes of copra/ha/year in different parts of the country for cultivation in different agroclimatic regions within the country, including varieties tolerant to biotic and abiotic stress and specific end uses.